Group B streptococcus late-onset disease,contaminated breast milk and mothers persistently GBS negative: report of 3cases - Giangiacomo Nicolini; Martina Borellini; Vitaliana Loizzo; Roberta Creti; Luigi Memo; Alberto Berardi (BMC, 2018)
Abstract Background Human milk is fundamental for its nutritional properties and to protect newborns, but it is not sterile and can sometime transmit bacteria. Few anecdotal cases suggest that breast milk could be a possible source of group B Streptococcus (GBS) late onset disease, although the pathogenesis is not entirely understood. Case presentation We report 3 cases of GBS late onset disease in full-term newborns. Fresh breast milk cultures yielded GBS, but mothers of neonates had no signs of mastitis and remained persistently GBS negative at rectovaginal site. Conclusions Breast milk containing group B Streptococcus can be a risk factor for late onset disease. The persistent negative maternal GBS status supports the assumption that newborns, colonised in the throat, could be the initial source of GBS, while the mammary gland could act as a GBS replication site. It is unclear whether a low bacterial load may represent only contamination rather than true milk infection.